Efficacy of Spinetoram Against Red Flour Beetle, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) - DERİCİ, Muhsin Yunus and FERİZLİ, Ahmet Güray and; Cİ, Mevlüt (ISPEC Tarım Bilimleri Dergisi, 2024)
This study, conducted at Department of Plant Protection, Faculty of Agriculture, Ankara University, aimed to evaluate the efficacy of Spinetoram (Radiant 120 SC) against the red flour beetle, Tribolium castaneum, across three temperatures (20, 25, and 30 °C) and at 65% relative humidity. Adults of T. castaneum were exposed to soft wheat treated with Spinetoram at concentrations of 0.01, 0.25, 0.50, 0.75, 1.00, 2.00, 5.00, and 10.00 ppm in PVC vials for of 1, 2, 3, 7, and 15 days. Bioassays at each dose rates were repeated 3 times with three replicates each. Adult mortality data were analyzed by repeated measures analysis of variance technique and the differences between the means were determined by Tukey’s test. Mortality rates were found to be proportional to the dose, temperature, and exposure time. At 0.01, 0.25, 0.5, and 0.75 ppm doses, mortality rates were similar to those of the controls. At 1 ppm dose, mortality rates were 37.04 %, 52.59 %, and 72.59 % after 15 days of exposure at 20, 25 and 30 °C, respectively. The mortalities were 80.74 %, 68.52 % and 81.85 % at 2 ppm dose, 92.59 %, 98.15 %, 90.37 % at 5 ppm dose, and 98.89 %, 99.26 % and 99.63 % at 10 ppm dose, respectively. The development of F1 adults was significantly suppressed at 2 ppm, with the suppression rates of 80.0 %, 63.7 %, and 45.3 % at 20, 25, and 30 °C, respectively. In conclusion, Spinetoram can be considered as an alternative to chemical protectants in the control of T. castaneum.